Amphiphilic Cu-coated ZSM-5 molecular sieve monatomic catalyst capable of forming high-stability emulsion and preparation method of amphiphilic Cu-coated ZSM-5 molecular sieve monatomic catalyst

By preparing amphiphilic Cu@ZSM-5 molecular sieve single-atom catalysts, the problems of poor dispersibility and low activity of traditional catalysts in oil-water two-phase catalytic reactions were solved, achieving efficient oil-water phase reactions and stable emulsion formation.

CN121103428APending Publication Date: 2025-12-12JILIN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511275385.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-08
Publication Date
2025-12-12

AI Technical Summary

Technical Problem

Traditional catalysts suffer from low mass transfer efficiency, slow reaction rate, and difficulty in catalyst recovery in oil-water two-phase catalytic reactions. Furthermore, single-atom catalysts are prone to agglomeration and deactivation on hydrophobic supports, and there is a lack of synergistic optimization strategies.

Method used

By precisely controlling the surface chemical properties of ZSM-5 molecular sieves and the coordination environment of copper species, a Cu@ZSM-5 molecular sieve single-atom catalyst with both amphiphilicity and high stability was prepared. This catalyst was used to form a highly stable emulsion in an oil-water system, thereby enhancing the contact of reactants.

Benefits of technology

It achieves high dispersibility and high activity of the catalyst in the oil-water system, and the catalyst has good stability. It can form a stable Pickering emulsion in the oil and water phases and maintain it without separation for several months.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121103428A_ABST
    Figure CN121103428A_ABST
Patent Text Reader

Abstract

The invention discloses an amphiphilic Cu-coated ZSM-5 molecular sieve monatomic catalyst capable of forming a high-stability emulsion and a preparation method of the amphiphilic Cu-coated ZSM-5 molecular sieve monatomic catalyst, and belongs to the technical field of emulsification. The preparation method comprises the following steps: firstly, preparing an ultra-small nanoscale ZSM-5 molecular sieve precursor, and then dispersing the ultra-small nanoscale ZSM-5 molecular sieve precursor in an ammonium nitrate aqueous solution to obtain the ZSM-5 molecular sieve capable of being used for metal loading; dispersing into a soluble salt water solution of Cu to obtain a copper-loaded molecular sieve; and finally, calcining in a hydrogen atmosphere to obtain the spherical nano Cu-coated ZSM-5 molecular sieve. And dispersing in toluene, and adding organosilane containing a hydrophilic group and organosilane containing an oleophylic group to obtain the amphiphilic Cu-coated ZSM-5 molecular sieve monatomic catalyst. The surface of the prepared catalyst contains hydrophilic and oleophylic groups at the same time, stable Pickering emulsion is formed in two phases composed of water and hexadecane, and the stable Pickering emulsion can be maintained for several months; the catalyst is low in cost, simple in preparation process and good in stability.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of emulsification, and particularly relates to a dual amphiphilic Cu@ZSM-5 molecular sieve monatomic catalyst capable of forming a high-stability emulsion and a preparation method thereof. BACKGROUND

[0002] In recent years, with the development of green chemistry and sustainable chemical industry, oil-water two-phase catalytic reactions (such as biomass conversion, organic pollutant degradation, and oil hydrogenation) have attracted widespread attention. However, due to the incompatibility between the oil phase and the water phase, traditional homogeneous or heterogeneous catalytic systems often face problems such as low mass transfer efficiency, slow reaction rate, and difficult catalyst recovery. Emulsion is an effective strategy to enhance the contact of reactants by constructing an oil-water emulsion interface. Traditional methods rely on the addition of surfactants or mechanical stirring to form emulsions, which are prone to phase separation, and the surfactants may contaminate the products or inhibit the catalytic activity. Single-atom catalysts have great potential in heterogeneous catalysis due to their extremely high atom utilization rate (close to 100%) and well-defined active sites. However, their application in two-phase catalytic systems is limited by insufficient interface contact due to the hydrophobicity of the support and the easy aggregation and deactivation of single atoms. In recent years, various types of interfacially active solid particles have been successfully prepared and applied, but existing research has focused on single functions (such as only enhancing emulsion stability or only optimizing catalytic activity), lacking a synergistic optimization strategy.

[0003] Molecular sieves are widely used in catalysis due to their regular pore channels and adjustable acidity, but traditional molecular sieves are highly hydrophobic and difficult to stabilize emulsions. Therefore, it is of great significance to prepare a molecular sieve-based dual amphiphilic single-atom catalyst in a two-phase system. SUMMARY

[0004] To solve the above technical problems, the application provides a catalyst with dual amphiphilicity and high-stability single-atom sites and a preparation method thereof by precisely regulating the surface chemical properties of the molecular sieve and the coordination environment of the copper species.

[0005] The preparation method of the dual amphiphilic Cu@ZSM-5 molecular sieve monatomic catalyst capable of forming a high-stability emulsion comprises the following steps:

[0006] (1) Preparation of nanoscale ZSM-5 molecular sieve: sodium hydroxide, aluminum source, silicon source, amino acid are dispersed in aqueous solution of tetrapropylammonium hydroxide in turn, after fully stirring and mixing uniformly, reaction under hydrothermal conditions at 50-100℃ for 24-96h, then reaction under hydrothermal conditions at 150-200℃ for 12-36h, after centrifugation, the obtained product is washed and dried, finally calcination at 500-600℃ for 6-10h, to obtain 30-60nm particle size of ultra-small nanoscale ZSM-5 molecular sieve precursor;

[0007] (2) The ZSM-5 nanomolecular sieve prepared in step (1) is dispersed in aqueous solution of ammonium nitrate, and reacted at 60-80℃ for 10-15h, after centrifugation, the obtained product is washed and dried, to obtain ZSM-5 molecular sieve which can be used for metal loading;

[0008] (3) The ZSM-5 molecular sieve which can be used for metal loading prepared in step (2) is dispersed into aqueous solution of soluble salt of Cu according to the mass ratio of 1:40-60, then stirred at 25-80℃ for 16-24h, after filtration separation and drying for 6-12h, to obtain copper-loaded molecular sieve;

[0009] (4) The copper-loaded molecular sieve prepared in step (3) is calcined under hydrogen atmosphere, to obtain spherical nanometer Cu@ZSM-5 molecular sieve;

[0010] (5) The spherical nanometer Cu@ZSM-5 molecular sieve prepared in step (4) is dispersed in toluene, a certain proportion of organic silane containing hydrophilic group and organic silane containing lipophilic group are added, reaction at 60-110℃ for 10-24h, after centrifugation, the obtained product is washed and dried, to obtain the amphiphilic Cu@ZSM-5 molecular sieve monatomic catalyst.

[0011] Further, the molar ratio of the amount of tetrapropylammonium hydroxide, sodium hydroxide, aluminum source, silicon source, amino acid and H2O in step (1) is 54-216:1.8-7.2:1:120-480:12-36:1080-4320;

[0012] Further, the aluminum source in step (1) is one of aluminum isopropoxide and aluminum sulfate octadecahydrate;

[0013] Further, the silicon source in step (1) is one of tetraethyl orthosilicate and silica gel;

[0014] Further, the amino acid in step (1) is one or more of glycine, lysine or glutamic acid;

[0015] Further, the molar ratio of the amount of ZSM-5 nanomolecular sieve and ammonium nitrate in step (2) is 1:10-30;

[0016] Further, the step (2) is centrifuged at 10000-12000 rpm for 3-5 minutes, and the washing is first washed with water for 3-5 times and then washed with ethanol for 1-2 times;

[0017] Further, the soluble salt of Cu in the step (3) can be one of copper nitrate, copper chloride, copper sulfate and copper acetate;

[0018] Further, the molar ratio of Cu to the ZSM-5 molecular sieve that can be used for metal loading in the step (3) is 1:100-200;

[0019] Further, the calcination temperature in the step (4) is 100-400℃, and the calcination time is 1-2h;

[0020] Further, the molar ratio of toluene to the spherical nano Cu@ZSM-5 molecular sieve in the step (5) is 100-120:1;

[0021] Further, the step (5) is centrifuged at 6000-9000 rpm for 1-2 minutes, and the washing is first washed with toluene for 3-5 times and then washed with chloroform for 2-3 times;

[0022] Further, the structure formula of the organosilane containing a hydrophilic group in the step (5) is as follows,

[0023] (RO) a -Si-(R1) 4-a or X-Si-(R1) 4-a

[0024] wherein, R is -CH3, -C2H5 or H; R1 is a hydrophilic group such as -NH2, -COOH, -CN or -SH; X is halogen; and a is 1, 2 or 3;

[0025] Further, the structure formula of the organosilane containing an oleophilic group in the step (5) is as follows,

[0026] (R * O) b -Si-R *1 4-b or Y-Si-R *1 4-b

[0027] wherein, R * is -CH3, -C2H5 or H; R *1 is an oleophilic group such as -CH3, -C2H5, -C3H7, -C4H9, -C5H 11 , -C6H 13 , -C8H 17 , etc.; Y is halogen; and b is 1, 2 or 3;

[0028] Furthermore, in step (5), the molar ratio of organosilane containing hydrophilic groups to organosilane containing lipophilic groups is 1.5 to 19:1; the molar ratio of spherical nano Cu@ZSM-5 molecular sieve to organosilane containing hydrophilic groups is 0.5 to 0.05:1.

[0029] In the preferred embodiment, the molecular sieve particle size is concentrated at 50 nm, and Cu is the active component, uniformly dispersed on the support in a single-atom state, with a loading of 0.64 wt% in the catalyst (corresponding to Example 1). The catalyst surface contains both hydrophilic and lipophilic groups, forming a stable Pickering emulsion in a two-phase mixture of water and hexadecane, which can be maintained for several months, with an emulsion bubble size of approximately 30 micrometers. This invention has extremely low preparation cost, a simple preparation process, and good catalyst stability. Attached Figure Description

[0030] Figure 1 Transmission electron microscope (TEM) images and elemental distribution diagrams of the amphiphilic Cu@ZSM-5 molecular sieve single-atom catalyst obtained in Example 1;

[0031] Figure 2 XRD pattern of the amphiphilic Cu@ZSM-5 molecular sieve single-atom catalyst obtained in Example 1;

[0032] Figure 3 : Nitrogen adsorption and desorption diagram of the amphiphilic Cu@ZSM-5 molecular sieve single-atom catalyst obtained in Example 1;

[0033] Figure 4 XPS image of the amphiphilic Cu@ZSM-5 molecular sieve single-atom catalyst obtained in Example 1;

[0034] Figure 5 Infrared image of the amphiphilic Cu@ZSM-5 molecular sieve single-atom catalyst obtained in Example 1 (inset is a magnified view of the local area within the red box);

[0035] Figure 6 Emulsification effect diagram of the amphiphilic Cu@ZSM-5 molecular sieve single-atom catalyst obtained in Example 1;

[0036] Figure 7 Emulsion bubble image of the amphiphilic Cu@ZSM-5 molecular sieve single-atom catalyst obtained in Example 1 using Leica electron microscopy;

[0037] Figure 8 Emulsification effect diagram of Cu@ZSM-5 molecular sieve single-atom catalyst obtained in Example 3;

[0038] Figure 9 Emulsion bubble image of the amphiphilic Cu@ZSM-5 molecular sieve single-atom catalyst obtained in Example 4 using Leica electron microscopy. Detailed Implementation

[0039] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the embodiments will be described in more detail and completely below. It should be noted that the embodiments described below are not all embodiments, but only embodiments of the preferred inventive conditions of the present invention. The reagents and instruments used in the embodiments can all be purchased through normal commercial channels. Based on the embodiments of the present invention, those skilled in the art can directly obtain these embodiments without creative activity, and these embodiments fall within the scope of protection of the present invention.

[0040] Example 1

[0041] (1) Preparation of nano-sized ZSM-5 molecular sieve: 0.12g sodium hydroxide, 0.172g aluminum isopropoxide, 22.4mL tetraethyl orthosilicate and 1.46g lysine were dispersed in 36.6mL of 25% tetrapropylammonium hydroxide aqueous solution. After thorough mixing, the mixture was reacted at 70℃ for 48h under hydrothermal conditions, and then reacted at 170℃ for 24h under hydrothermal conditions. After centrifugation, the product was washed with pure water and dried. Finally, it was calcined at 550℃ for 6h to obtain 6.2g of nano-sized ZSM-5 molecular sieve precursor with a particle size of 50nm.

[0042] (2) Disperse 1g of ZSM-5 nanomolecular sieve with a particle size of 50nm prepared in step (1) in 30mL of 1M ammonium nitrate aqueous solution, react at 80℃ for 12h, centrifuge at 10000rpm for 4 minutes, wash with water 4 times and ethanol once, and dry to obtain 1.02g of ZSM-5 nanomolecular sieve that can be used for metal loading.

[0043] (3) Disperse 1g of ZSM-5 molecular sieve prepared in step (2) into an aqueous solution of copper acetate at a mass ratio of 1:50. The molar ratio of copper to ZSM-5 nano molecular sieve is 1:100. Stir at room temperature for 24h, filter and separate, and dry for 8h to obtain 1.05g of copper-loaded molecular sieve.

[0044] (4) The 1.05g copper-loaded molecular sieve prepared in step (3) was calcined in a hydrogen atmosphere for 2h at a calcination temperature of 200℃ to obtain 1.05g spherical nano Cu@ZSM-5 molecular sieve.

[0045] (5) Disperse 1g of spherical Cu@ZSM-5 molecular sieve prepared in step (4) in 50mL of toluene, and add 42.6µL of γ-aminopropyltriethoxysilane (C9H) 23NO3Si) and 390 μL of hexyltriethoxysilane (C 12 H 28 O3Si) was reacted at 110℃ for 20 h, centrifuged at 9000 rpm for 1 minute, washed 3 times with toluene, washed twice with chloroform, and dried to obtain 1.02 g of amphiphilic Cu@ZSM-5 molecular sieve single-atom catalyst with a copper loading of 0.64 wt%. 25 mg of amphiphilic Cu@ZSM-5 molecular sieve single-atom catalyst was added to 10 mL of aqueous phase and 10 mL of n-hexadecane system, sonicated for 30 minutes (frequency 40 kHz), and allowed to stand for 24 hours to observe emulsion stability and emulsion bubble size.

[0046] Figure 1 The image shows a transmission electron microscope (TEM) image and elemental distribution diagram of the amphiphilic Cu@ZSM-5 molecular sieve single-atom catalyst material. It can be seen that the average particle diameter of the obtained catalyst is 50 nm, and it contains silicon, aluminum and copper elements, with copper active sites evenly distributed. Figure 2 The image shows the XRD pattern of the amphiphilic Cu@ZSM-5 molecular sieve single-atom catalyst. The characteristic diffraction peaks of the MFI structure can be seen, indicating that the crystal structure of the molecular sieve was not destroyed during the catalyst preparation process. Figure 3 The nitrogen adsorption-desorption curve of the amphiphilic Cu@ZSM-5 molecular sieve single-atom catalyst shows no obvious hysteresis loop and the adsorption capacity increases sharply when P / P0 is very low, which proves that the material only has a microporous structure. Figure 4 The XPS data results for the amphiphilic Cu@ZSM-5 molecular sieve single-atom catalyst are shown. The peaks at 963 eV and 944 eV are obvious satellite peaks, proving the presence of +2 copper. The peak at 933.4 eV is the characteristic peak of Cu+, and the peak at 935.7 eV is the characteristic peak of Cu2+. It can be seen that the active copper in the material is a mixed distribution of +1 and +2 valence. Figure 5 This is the infrared (IR) spectrum of the amphiphilic Cu@ZSM-5 molecular sieve single-atom catalyst, 2959 cm⁻¹. -1 and 2875cm -1 The peak at 3320 cm⁻¹ corresponds to the stretching vibration of the CH bond in the methyl group, indicating successful modification of the zeolite surface with hexyltriethoxysilane. -1 The characteristic peak observed at the point corresponds to the stretching vibration of the amino group, which proves that the amino functional group was successfully introduced. Figure 6 This is an emulsification effect diagram of the amphiphilic Cu@ZSM-5 molecular sieve single-atom catalyst. In the water / hexadecane system, the emulsion layer formed occupies the entire oil phase and part of the water phase, forming a stable Pickering emulsion. Figure 7This is a Leica electron microscope image of emulsion bubbles after adding amphiphilic Cu@ZSM-5 molecular sieve single-atom catalyst material to the water / hexadecane system. It can be seen that the emulsion layer accounts for more than 70%, and the emulsion bubbles are uniform in size, with the diameter concentrated at 30μm.

[0047] Example 2

[0048] (1) Preparation of nano-sized ZSM-5 molecular sieve: 0.12g sodium hydroxide, 0.172g aluminum isopropoxide, 22.4mL tetraethyl orthosilicate and 1.46g lysine were dispersed in 36.6mL of 25% tetrapropylammonium hydroxide aqueous solution. After thorough mixing, the mixture was reacted at 70℃ for 48h under hydrothermal conditions, and then reacted at 170℃ for 24h under hydrothermal conditions. After centrifugation, the product was washed with pure water and dried. Finally, it was calcined at 550℃ for 6h to obtain 6.2g of nano-sized ZSM-5 molecular sieve precursor with a particle size of 50nm.

[0049] (2) Disperse 1g of ZSM-5 nanomolecular sieve with a diameter of 50nm prepared in step (1) in 30mL of 1M ammonium nitrate aqueous solution, react at 80℃ for 12h, centrifuge at 10000rpm for 4 minutes, wash with water 4 times and ethanol once, and dry to obtain 1.02g of ZSM-5 nanomolecular sieve that can be used for metal loading.

[0050] (3) Disperse 1g of ZSM-5 molecular sieve prepared in step (2) into an aqueous solution of copper nitrate at a mass ratio of 1:50. The molar ratio of copper to ZSM-5 nano molecular sieve is 1:100. Stir at 80℃ for 24h, filter and separate, and dry for 8h to obtain 1.06g of copper-loaded molecular sieve.

[0051] (4) The 1.06g copper-loaded molecular sieve prepared in step (3) was calcined in a hydrogen atmosphere for 2h at a calcination temperature of 400℃ to obtain 1.06g spherical nano Cu@ZSM-5 molecular sieve.

[0052] (5) Disperse 1g of spherical Cu@ZSM-5 molecular sieve prepared in step (4) in 50mL of toluene, and add 42.6µL of γ-aminopropyltriethoxysilane (C9H) 23 NO3Si) and 390 μL of hexyltriethoxysilane (C 12 H 28O3Si) was reacted at 110℃ for 20 h, centrifuged at 9000 rpm for 1 minute, washed 3 times with toluene, washed twice with chloroform, and dried to obtain 1.02 g of amphiphilic Cu@ZSM-5 molecular sieve single-atom catalyst with a copper loading of 1.06 wt%. 25 mg of amphiphilic Cu@ZSM-5 molecular sieve single-atom catalyst was added to 10 mL of aqueous phase and 10 mL of n-hexadecane system, sonicated for 30 minutes (frequency 40 kHz), and allowed to stand for 24 hours. The size of the emulsion bubbles was observed to be about 30 μm.

[0053] Example 3

[0054] (1) Preparation of nano-sized ZSM-5 molecular sieve: 0.12g sodium hydroxide, 0.172g aluminum isopropoxide, 22.4mL tetraethyl orthosilicate and 1.46g lysine were dispersed in 36.6mL of 25% tetrapropylammonium hydroxide aqueous solution. After thorough mixing, the mixture was reacted at 70℃ for 48h under hydrothermal conditions, and then reacted at 170℃ for 24h under hydrothermal conditions. After centrifugation, the product was washed with pure water and dried. Finally, it was calcined at 550℃ for 6h to obtain 6.2g of nano-sized ZSM-5 molecular sieve precursor with a particle size of 50nm.

[0055] (2) Disperse 1g of ZSM-5 nanomolecular sieve with a diameter of 50nm prepared in step (1) in 30mL of 1M ammonium nitrate aqueous solution, react at 80℃ for 12h, centrifuge at 10000rpm for 4 minutes, wash with water 4 times and ethanol once, and dry to obtain 1.02g of ZSM-5 nanomolecular sieve that can be used for metal loading.

[0056] (3) Disperse 1.02g of ZSM-5 molecular sieve prepared in step (2) into an aqueous solution of copper acetate at a mass ratio of 1:50. The molar ratio of copper to ZSM-5 nano molecular sieve is 1:100. Stir at room temperature for 24h, filter and separate, and dry for 8h to obtain 1.05g of copper-loaded molecular sieve.

[0057] (4) The 1.05g copper-loaded molecular sieve prepared in step (3) was calcined for 2 hours in a hydrogen atmosphere at a temperature of 400℃ to obtain 1.05g Cu@ZSM-5 molecular sieve single-atom catalyst with a copper loading of 0.64wt%. 25mg Cu@ZSM-5 molecular sieve single-atom catalyst was added to 10mL of aqueous phase and 10mL of n-hexadecane system and sonicated for 30 minutes (frequency 40kHz). The emulsification effect was very poor, the emulsion layer was unstable, and it quickly demulsified. Figure 8 As shown, the catalyst was not surface-modified with amphiphilic agents, therefore it lacks amphiphilicity and has poor emulsification effect.

[0058] Example 4

[0059] (1) Preparation of nano-sized ZSM-5 molecular sieve: 0.12g sodium hydroxide, 0.172g aluminum isopropoxide, 22.4mL tetraethyl orthosilicate and 1.46g lysine were dispersed in 36.6mL of 25% tetrapropylammonium hydroxide aqueous solution. After thorough mixing, the mixture was reacted at 70℃ for 48h under hydrothermal conditions, and then reacted at 170℃ for 24h under hydrothermal conditions. After centrifugation, the product was washed with pure water and dried. Finally, it was calcined at 550℃ for 6h to obtain 6.2g of nano-sized ZSM-5 molecular sieve precursor with a particle size of 50nm.

[0060] (2) Disperse 1g of ZSM-5 nanomolecular sieve with a diameter of 50nm prepared in step (1) in 30mL of 1M ammonium nitrate aqueous solution, react at 80℃ for 12h, centrifuge at 10000rpm for 4 minutes, wash with water 4 times and ethanol once, and dry to obtain 1.02g of ZSM-5 nanomolecular sieve that can be used for metal loading.

[0061] (3) Disperse 1g of ZSM-5 molecular sieve prepared in step (2) into an aqueous solution of copper nitrate at a mass ratio of 1:50. The molar ratio of copper to ZSM-5 nano molecular sieve is 1:200. Stir at 80°C for 24h, filter and separate, and dry for 8h to obtain 1.04g of copper-loaded molecular sieve.

[0062] (4) The 1.04g copper-loaded molecular sieve prepared in step (3) was calcined in a hydrogen atmosphere for 2h at a calcination temperature of 400℃ to obtain 1.04g spherical nano Cu@ZSM-5 molecular sieve.

[0063] (5) Disperse 1g of spherical Cu@ZSM-5 molecular sieve prepared in step (4) in 50mL of toluene, and add 21.3µL of γ-aminopropyltriethoxysilane (C9H) 23 NO3Si) and 411 μL of n-octyltriethoxysilane (C 12 H 28 O3Si), reacted at 60℃ for 20h, centrifuged at 9000rpm for 1 minute, washed three times with toluene, washed twice with chloroform, and dried to obtain 1.01g of amphiphilic Cu@ZSM-5 molecular sieve single-atom catalyst with a copper loading of 0.48wt%. 25mg of the amphiphilic Cu@ZSM-5 molecular sieve single-atom catalyst was added to 10mL of aqueous phase and 10mL of n-hexadecane system, sonicated for 30 minutes (frequency 40kHz), and allowed to stand for 24 hours. The emulsion layer accounted for approximately 45%. Figure 9 As shown, the size of the emulsion bubbles is approximately 40 μm.

Claims

1. A method for preparing an amphiphilic Cu@ZSM-5 molecular sieve single-atom catalyst capable of forming a highly stable emulsion, characterized in that: The steps are as follows: (1) Preparation of nanoscale ZSM-5 molecular sieve: Sodium hydroxide, aluminum source, silicon source and amino acid are sequentially dispersed in tetrapropylammonium hydroxide aqueous solution. After thorough stirring and mixing, the mixture is reacted under hydrothermal conditions at 50-100℃ for 24-96h, and then reacted under hydrothermal conditions at 150-200℃ for 12-36h. After centrifugation, the obtained product is washed and dried, and finally calcined at 500-600℃ for 6-10h to obtain ultra-small nanoscale ZSM-5 molecular sieve precursor with a particle size of 30-60nm. (2) Disperse the ZSM-5 nano molecular sieve prepared in step (1) in an ammonium nitrate aqueous solution, react at 60-80℃ for 10-15h, centrifuge, wash and dry the product to obtain ZSM-5 molecular sieve that can be used for metal loading. (3) Disperse the ZSM-5 molecular sieve prepared in step (2) into a Cu-soluble salt aqueous solution at a mass ratio of 1:40 to 60, stir at 25 to 80°C for 16 to 24 hours, filter and separate, and dry for 6 to 12 hours to obtain a copper-loaded molecular sieve. (4) The copper-loaded molecular sieve prepared in step (3) was calcined in a hydrogen atmosphere to obtain spherical nano Cu@ZSM-5 molecular sieve. (5) The spherical nano-Cu@ZSM-5 molecular sieve prepared in step (4) is dispersed in toluene, and a certain proportion of organosilane containing hydrophilic groups and organosilane containing lipophilic groups are added. The reaction is carried out at 60-110℃ for 10-24h. After centrifugation, the resulting product is washed and dried to obtain the amphiphilic Cu@ZSM-5 molecular sieve single-atom catalyst.

2. The method for preparing an amphiphilic Cu@ZSM-5 molecular sieve single-atom catalyst capable of forming a highly stable emulsion as described in claim 1, characterized in that: In step (1), the molar ratio of tetrapropylammonium hydroxide, sodium hydroxide, aluminum source, silicon source, amino acid, and H2O is 54–216:1.8–7.2:1:120–480:12–36:1080–4320; the aluminum source is either aluminum isopropoxide or aluminum sulfate octadecyl hydrate; the silicon source is either tetraethyl orthosilicate or silica gel; and the amino acid is one or more of glycine, lysine, or glutamic acid.

3. The method for preparing an amphiphilic Cu@ZSM-5 molecular sieve single-atom catalyst capable of forming a highly stable emulsion as described in claim 1, characterized in that: In step (2), the molar ratio of ZSM-5 nano molecular sieve to ammonium nitrate is 1:10-30; centrifugation is performed at 10000-12000 rpm for 3-5 minutes; washing is performed by first washing with water 3-5 times and then washing with ethanol 1-2 times.

4. The method for preparing an amphiphilic Cu@ZSM-5 molecular sieve single-atom catalyst capable of forming a highly stable emulsion as described in claim 1, characterized in that: In step (3), the soluble salt of Cu can be one of copper nitrate, copper chloride, copper sulfate, or copper acetate; the molar ratio of Cu to ZSM-5 molecular sieve that can be used for metal loading is 1:100 to 200.

5. The method for preparing an amphiphilic Cu@ZSM-5 molecular sieve single-atom catalyst capable of forming a highly stable emulsion as described in claim 1, characterized in that: In step (4), the calcination temperature is 100-400℃ and the calcination time is 1-2h.

6. The method for preparing an amphiphilic Cu@ZSM-5 molecular sieve single-atom catalyst capable of forming a highly stable emulsion as described in claim 1, characterized in that: In step (5), the molar ratio of toluene to spherical nano Cu@ZSM-5 molecular sieve is 100-120:1; the centrifugation speed is 6000-9000 rpm and the centrifugation time is 1-2 minutes; the washing is to first wash with toluene 3-5 times and then wash with chloroform 2-3 times.

7. The method for preparing an amphiphilic Cu@ZSM-5 molecular sieve single-atom catalyst capable of forming a highly stable emulsion as described in claim 1, characterized in that: The structural formula of the organosilane containing hydrophilic groups in step (5) is shown below. (RO) a -Si-(R1) 4-a OrX-Si-(R1) 4-a Where R is -CH3, -C2H5 or H; R1 is a hydrophilic group such as -NH2, -COOH, -CN or -SH; X is a halogen; and a is 1, 2 or 3.

8. The method for preparing an amphiphilic Cu@ZSM-5 molecular sieve single-atom catalyst capable of forming a highly stable emulsion as described in claim 1, characterized in that: The structural formula of the organosilane containing a lipophilic group in step (5) is shown below. (R * O) b -Si-R *1 4-b or Y-Si-R *1 4-b Among them, R * -CH3, -C2H5, or H; R *1 -CH3, -C2H5, -C3H7, -C4H9, -C5H 11 -C6H 13 -C8H 17 Equal lipophilic groups; Y is a halogen; b is 1, 2 or 3.

9. The method for preparing an amphiphilic Cu@ZSM-5 molecular sieve single-atom catalyst capable of forming a highly stable emulsion as described in claim 1, characterized in that: In step (5), the molar ratio of organosilanes containing hydrophilic groups to organosilanes containing lipophilic groups is 1.5 to 19:1; the molar ratio of spherical nano Cu@ZSM-5 molecular sieves to organosilanes containing hydrophilic groups is 0.5 to 0.05:

1.

10. A single-atom catalyst of amphiphilic Cu@ZSM-5 molecular sieve capable of forming highly stable emulsions, characterized in that: It is prepared by the preparation method described in any one of claims 1 to 9.